The utility of FDG-PET for detecting multiple primary cancers in hypopharyngeal cancer patients - Kaida, H.; Ishibashi, M.; Kurata, S.; Uchiyama, Y.; Tanaka, N.; Abe, T.; Kobayashi, M.; Kaibara, H.; Uchida, M.; Nakashima, T.; Fujita, H.; Hayabuchi, N. (Onkologische Welt, 2010)
Aim: To examine the utility of 2’-[18F]-fluoro-2’-deoxy-D-glucose positron emission tomography (FDG-PET) for detecting multiple primary cancers (MPC) in patients with hypopharyngeal cancer (HPC). Patients, methods: Seventy patients with HPC underwent FDG-PET to determine the staging. Routine clinical examinations were carried out, including computed tomography (CT), magnetic resonance imaging (MRI), ultrasound (US), and oesophagealgastroduodenoscopy (EGDS). The detection rate of synchronous and metachronous cancer was calculated based on FDG-PET alone or FDG-PET combined with clinical routine examination. Sensitivity, specificity, positive predictive values (PPV), negative predictive values (NPV), and accuracy were used to diagnose oesophageal cancer using FDG-PET. Results: Of the 70 patients, 12 (17.1%) had 15 synchronous tumours, and 2 of the 58 remaining patients (3.4%) had metachronous tumours. Oesophageal cancer was discovered most frequently: superficial type (n=6), advanced type (n=4). On a per-patient basis, 11 of 12 patients (91.6%) were diagnosed with synchronous tumours, and on a per-lesion basis, 12 of 15 lesions (80.0%) were detected by FDG-PET.The sensitivity, specificity, accuracy, PPV, and NPV of FDG-PET regarding oesophageal cancer were 70%, 100%, 95.7%, 100%, and 95.2% respectively. Three of the six superficial types were positive on FDG-PET. Both of the metachronous tumour lesions were detected by FDG-PET. Conclusion: FDG-PET is useful for estimating the MPC in HPC patients. Since 3 of 10 synchronous oesophageal cancer were missed with PET alone, a combination with EGDS should be considered to exclude synchronous oesophageal cancer.
Keywords: Hypopharyngeal cancer; FDG-PET; multiple primary cancer; oesophageal cancer